Development of family income since the 1990s: A fresh look at German microdata using income-dependent equivalence scales - Jan Marvin Garbuszus; Notburga Ott; Sebastian Pehle; Martin Werding (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Income inequality and poverty risks receive a lot of attention in public debates and current research. However, the situation of families that di?er in size and composition is rarely considered more closely in this context. Relevant research typically relies on equivalence scales to make income comparable across di?erent types of households. The standard approach for doing so is based on the so-called "(modi?ed) OECD scale". Instead, we apply income-dependent equivalence scales in this paper to assess how the ?nancial situation of families living in Germany has developed since the early 1990s. Among other things, our results indicate that poverty risks for households with children - especially for single parents - are considerably higher than was previously found. We conclude that the application of income-dependent equivalence scales is required for applied research in income inequality, especially if one is concerned with the composition, not just the size of the population at poverty risk.
Keywords: D12; I32; J12; 330; equivalence scales; family income; household needs; inequality measurement; poverty risks